2012
DOI: 10.1371/journal.pone.0030275
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Efficacy and Safety of Existing TNF Blocking Agents in Treatment of Rheumatoid Arthritis

Abstract: Background and ObjectivesFive-tumour necrosis factor (TNF)-blockers (infliximab, etanercept, adalimumab, certolizumab pegol and golimumab) are available for treatment of rheumatoid arthritis. Only few clinical trials compare one TNF-blocker to another. Hence, a systematic review is required to indirectly compare the substances. The aim of our study is to estimate the efficacy and the safety of TNF-blockers in the treatment of rheumatoid arthritis (RA) and indirectly compare all five currently available blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(153 citation statements)
references
References 63 publications
(23 reference statements)
3
138
0
8
Order By: Relevance
“…Furthermore, anti-TNF-α agents are more efficacious in promoting the clinical signs and symptoms of RA compared to MTX alone. Anti-TNF-α agents plus MTX show sustained efficacy and remain more effective compared to anti-TNF-α monotherapy (53). Compared to MTX and PBO, the ACR20, 50 and 70 response rates for 1-year treatment with MTX plus any of the TNF inhibitors were 60 vs. 25%, 40 vs. 10% and 20 vs. 5%, respectively (54).…”
Section: Similarity and Difference Between Anti-tnf Agentsmentioning
confidence: 99%
“…Furthermore, anti-TNF-α agents are more efficacious in promoting the clinical signs and symptoms of RA compared to MTX alone. Anti-TNF-α agents plus MTX show sustained efficacy and remain more effective compared to anti-TNF-α monotherapy (53). Compared to MTX and PBO, the ACR20, 50 and 70 response rates for 1-year treatment with MTX plus any of the TNF inhibitors were 60 vs. 25%, 40 vs. 10% and 20 vs. 5%, respectively (54).…”
Section: Similarity and Difference Between Anti-tnf Agentsmentioning
confidence: 99%
“…Moreover, infliximab can induce anti-drug antibodies which can interfere or even abolish the drug effectiveness [6]. As other anti-TNF-α agents, treatment with infliximab is associated with a significant increase of infections, including tuberculosis, bacterial, viral and parasite infections [7]. In 2001, an initial study on the efficacy of anti-TNF-α agents on inflammatory eye diseases was published by Smith et al who showed that both infliximab might benefit certain subgroups of patients with inflammatory eye disease [8].…”
Section: Infliximabmentioning
confidence: 99%
“…For many rheumatologic and autoinflammatory diseases, anti-tumor necrosis factor (TNF) α and anti-interleukin (IL) 1 biologics have proven effective in trials conducted over the last decades, and are now registered as first line therapies for many of these disorders [10,11]. In contrast to the situation regarding these autoimmune and inflammatory conditions, clinical testing of cytokine antagonists in T1D is in its infancy, with few reported studies and even fewer ongoing trials, as can be judged by the NIH register of clinical trials,…”
Section: Cytokines and Type 1 Diabetes: No Lack Of Candidate Targetsmentioning
confidence: 99%
“…Biologic TNFα antagonists include monoclonal antibodies raised against recombinant human TNFα (infliximab, adalimumab, and others) and a recombinant fusion protein between the soluble type 2/p75 TNFα receptor and the constant region of human immunoglobulin G1 (IgG1), termed etanercept [11] (Figure 1). In contrast to the IL-1 family, the TNF family does not include natural TNF receptor antagonists.…”
Section: Tnfα Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation